FUTURE CITY BASED ON SMART MOBILITY CONCEPT: CHARACTER AND BENCHMARKING - Wicaksana, Gde Bagus Andhika (Journal of Architectural Research and Education, 2020)
A city in overcoming its problem is defined as a smart product known as the smart city concept. Smart city has a conceptual definition as a city that is anticipatively able to manage resources in an innovative and competitive manner, with technological support in order to create a city that is comfortable and sustainable. One of the dimensions in smart city is smart mobility (transportation and infrastructure): Management of urban infrastructure that is developed in the future is an integrated and oriented management system to ensure alignments with the public interest. This study uses a critical review approach with a descriptive analysis method which is carried out by examining an urban problem in general and the theory of smart city through the search for ideas in the literature with the focus of this research is to define the character of smart mobility so that from defining the character, a solution is obtained about the indicator and expectations that are fulfilled to realize a city that has a smart mobility character. Through these methods, characters are generated from a smart city that is responsive, innovative and competitive. From these criteria produce a matrix to explain smart mobility consisting of aspects concerning aspects of less mobility, move freely, and less travel time. From the existence of the character and the matrix is finally cascaded to an indicator of the benchmarking toward smart mobility of a city.Keywords â€“ Smart Mobility, less mobility, move freely, and less travel timeÂ